Pesantren dan Lahirnya Diskursus Moderasi Beragama di Indonesia - Ria Ratna Ningtyas; Abdul Khobir (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2025)
This article aims to analyze the role of pesantren in initiating and maintaining the discourse of religious moderation in the complex context of Indonesia. Using a descriptive-analytical approach based on literature research, the article illustrates the contribution of pesantren in maintaining social harmony and its relevance in developing an inclusive religious moderation discourse. Based on the analysis, the article concludes that pesantren, as the oldest Islamic educational institution in Indonesia, plays a strategic role in building and practicing religious moderation. Pesantren not only serve as a stronghold against radicalism but also create an inclusive religious discourse through education that emphasizes the values of tawasuth (moderation), tasamuh (tolerance), and i’tidal (justice). However, contemporary dynamics present pesantren with challenges such as the emergence of transnational ideologies and religious polarization. Keywords: Pesantren; Dicourse; Religious Moderation; Indonesia